The crowdsourced performance review : how to use the power of social recognition to transform employee performance - Mosley, Eric (McGraw-Hill Education, 2013)
Showing you how to create a review system that gathers the feedback of many; so you can make better; more informed decisions; this book provides the key to seizing your company's competitive edge with a new ground-breaking performance management system. --